Geographic and socioeconomic variation in healthcare: Evidence from migration - Petér S. Elek; Anita Győrfi; Nóra Kungl; Daniel Prinz (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
We study variation in healthcare utilization across geographies and socioeconomic groups in Hungary. Exploiting migration across geographic regions and relying on high-quality administrative data on healthcare use and income we show that the role of place-specific supply factors is heterogeneous across types of care and across socioeconomic groups. Overall, place-specific factors account for 68% of the variation in outpatient spending and 35% of the variation in drug spending, but almost none of the variation in inpatient spending. Place effects explain four-fifth of outpatient spending variation for non-employed working-age individuals, but less than two-fifth for individuals with above-median wage incomes. There is a positive association between place effects and outpatient capacity, especially for low-income individuals. These results suggest that access to healthcare varies especially for low-income people even in a context with universal coverage.
Keywords: I11; I14; C23; 330; healthcare utilization; healthcare supply; regional variation; socioeconomic status